Hubungan Gerakan Sholat Dengan Keluhan Nyeri Punggung Bawah Myogenik Pada Wanita Lanjut Usia - Sari, Risky Novita; , Wahyuni, S.Fis.,Ftr.,M.Kes; , Totok Budi Santoso, S.Fis.,Ftr.,MPH (2015)
Background : Lower Back Pain Myogenik is lower back pain caused by disorders or abnormalities of the musculoskeletal without neurological disorders between vertebrae thoracal 12 to bottom of the hip or anus. The process of aging in elderly marked decrease in body functions, among others reduced flexibility vertebrae and cause pain. There is movement on the prayer movement bowing and prostaction, where there movement will happen stretching on lumbar vertebrae so that the postural muscle to be stretched. Flexibility would be beneficial to reduce pain lower back pain in older women. Objective of Research : To know the relationship of prayer movement with lower back pain complaint In elderly women. Method of Research : with the approach of case control and observational study designs. The population in this study were in elderly women in Posyandu Lansia Abadi V Nilasari, Kec. Kartasura Kab. Sukoharjo 49-79 years old . Total sampel of 35 respondents. Result were analyzed using Chi Square Test. Result of the Research : Chi Square Test results showed p = 0,044 < 0,05 which means there is a significant relationship between prayer movement with low back pain myogenik in elderly woman. Conclusion: In this study can conclude that there is a relationship prayer movement with low back pain myogenic in elderly women. People who curry out the daily prayer movement capable of protecting 4 time no NPB myogenic pain with those who do not pray Key word: prayer movement, lumbar back pain, women elderly